2016
DOI: 10.1039/c6ra08168a
|View full text |Cite
|
Sign up to set email alerts
|

Towards the development of uniform closed cell nanocomposite foams using natural rubber containing pristine and organo-modified nanoclays

Abstract: A closed cell rubber foam, based on a natural rubber (NR)/nanoclay nanocomposite, was produced using a one-step foaming process with compression molding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…The elongation at break of NRF/UG3 and NRF/CG3 were similar to that of unfilled NRF. Generally, the elongation at break of NRF composites decreased with increasing filler content due to the rigidity of fillers . However, in our case the addition of graphene particles does not impair the elongation at break of NRF nanocomposites, meaning that it can retain the elastic behavior of NRF product with high tensile strength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The elongation at break of NRF/UG3 and NRF/CG3 were similar to that of unfilled NRF. Generally, the elongation at break of NRF composites decreased with increasing filler content due to the rigidity of fillers . However, in our case the addition of graphene particles does not impair the elongation at break of NRF nanocomposites, meaning that it can retain the elastic behavior of NRF product with high tensile strength.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our case the addition of graphene particles does not impair the elongation at break of NRF nanocomposites, meaning that it can retain the elastic behavior of NRF product with high tensile strength. It can be concluded that NRF/CG3 exhibits high tensile strength while other fillers (such as carbon black [15,16] and organoclay [49,50]) cannot improve tensile strength of NRF composites at the same loading. Moreover, the elongation at break of natural rubber/graphene nanocomposite foam is similar to unfilled NRF product owing to low filler content.…”
Section: Morphology and Mechanical Properties Of Nr/graphene Nanocompmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that plastic waste is far more significant in volume respect than rubber waste, the latter still deserves a great deal of attention because it constitutes one group of materials imposing an environmental threat as they barely degrade by biological methods . Although today's technology development led to growing interest in the application of elastomers in several industries such as foams, electronics and electrical devices, as well as insulators, dampers, and sports equipment, the automobile industry is still the main consumer of rubber products in tires, engine parts, and fuel systems . The annual global production of tires is reported to be about 1.4 billion units .…”
Section: Introductionmentioning
confidence: 99%
“…3 Since these materials are not vulcanized so they can be recycle and re-shape via a re-melting process similar a thermoplastic materials. [5][6][7] Carbon nanotubes (CNTs) are known as the ideal reinforcing fillers to produce high-performance nanocomposites with excellent mechanical, thermal, and electrical properties 8,9 compared with other fillers such as glass fiber, talc, calcium carbonate, carbon black, and carbon nanofiber. [5][6][7] Carbon nanotubes (CNTs) are known as the ideal reinforcing fillers to produce high-performance nanocomposites with excellent mechanical, thermal, and electrical properties 8,9 compared with other fillers such as glass fiber, talc, calcium carbonate, carbon black, and carbon nanofiber.…”
Section: Introductionmentioning
confidence: 99%